Mengenali perspektif historis dan modern accounting - Dwi Urip Wardoyo; Denna Taris Citra Rahadiansyah; Naura Shofhah Ayuningtias; Deva Anggraeni Rahmadiah; Stefany Audia Putri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
Historical and modern perspectives in the field of accounting reflect developments and changes in the way we understand, use and organize financial information over the centuries.This study aims to find out how the development of accounting either from history and modern. The method used is the literatur review. The history of accounting begins with the existence of trade which is growing day by day so that better and more organized records are needed until the Paciolis’s Ledger appear, then in the 19th century double entry accounting has developed a lot. In the 20th century recording began using computer and when the world recession, modern accounting and accounting principles using the double entry aplicaton which lightened the workload of the finance department. Modern accounting was created because of old accounting, meaning that the two synergize and perfect each other until an effective and efficient accounting system is formed.